Beyond cytotoxic T cells: reprogrammed regulatory T cells help facilitate response to dual checkpoint blockade - Tullia C. Bruno; Anthony R. Cillo (Molecular Oncology)
Combination immunotherapies have entered the treatment armamentarium of oncology, but important knowledge gaps remain in our understanding of how these therapeutics work. A recent study by Rolig, Peng, and colleagues has shed new light on how dual blockade of PD1 and LAG3 enhances antitumor immunity. The authors first interrogated LAG3 expression on T cells across murine tumor models, classifying the models as LAG3hi or LAG3lo. Next, they found that LAG3hi models were unresponsive to anti‐PD1 alone but responsive to combination therapy with anti‐PD1 + anti‐LAG3. Surprisingly, the response to anti‐PD1 + anti‐LAG3 in LAG3hi models was associated with reprogramming of CD4+ regulatory T cells (Treg) from the canonically immunosuppressive state to an inflammatory state characterized by loss of expression of the transcription factor Foxp3 and upregulation of transcription factor Tbet. Importantly, an analogous reprogrammed Treg state was associated with response to anti‐PD1 + anti‐LAG3 and longer overall survival in patients with metastatic melanoma. This work highlights the importance of cells beyond cytotoxic CD8+ T cells as drivers of response to immunotherapy and sets the stage for subsequent mechanistic and translational studies.